PERBAIKAN SIFAT AGREGAT DENGAN BELERANG UNTUK MENINGKATKAN KINERJA CAMPURAN BERASPAL - Nurdajat, Dodi; Elkhasnet, Elkhasnet (Jurnal Teknik Sipil ITENAS, 2007)
A road is always needed as a transportation media because of that it’s hoped condition has a durability feet with the plan duration, so it’s attempted an increase of mixture pavement both the increase of road geometric and it’s pavement structure. In increasing the pavement structure sought a material alternative to be mixed with asphalt or aggregate. Aggregate is main component from road pavement structure. Aggregate used as mixture material of asphalt pavement. This research is aimed to observe the influence of sulfur to coarse aggregate characteristic which used LASTON AC-WC pavement mixture by Marshall method. This research used 60 penetration of asphalt. For specific gravity and absorption test of coarse aggregate was done a test of coarse aggregate mixed by sulfur based on percentage variation of sulfur to the coarse aggregate mass 5%, 10% and 15%. From the test of that coarse aggregate got 15% of the sulfur to the coarse aggregate mass  by absorption percentage 2,67%. The result of the mass test to the coarse aggregate mixed with sulfur gained the score of flow and VFA decreased. Meanwhile the score of stability, VMA VIM increased compared with the coarse aggregate without sulfur, it’s caused the aggregate hole filed by sulfur. Optimum asphalt content for the mixture of pavement with coarse aggregate without sulfur was 6,37% and aggregate mixed with sulfur was 15% of coarse aggregate wasn’t  gained the mass. Optimum asphalt  content of the test can be concluded that the coarse aggregate mixed  with sulfur needs more asphalt content